Evaluating a New Feeding Formula for Patients in the ICU Who Are Obese - Shuman, Jill (MD Conference Express, 2015)
This study evaluated a novel enteral formula designed especially for obese, critically ill patients. The formula contained 37% protein (as 100% whey hydrolysate) and 31% carbohydrate, along with medium-chain triglycerides, fish oil, and prebiotic fiber. Use of the study formula in obese patients may reduce hyperglycemia and facilitate nitrogen balance.